Comparison of three different reduction methods of the ankle mortise in unstable syndesmotic injuries - Vetter, Sven Y.; Beisemann, Nils; Keil, Holger; Schnetzke, Marc; Swartman, Benedict; Franke, Jochen; Grützner, Paul Alfred; Privalov, Maxim (Scientific reports, 2019)
In order to achieve a clinically satisfying result and to prevent posttraumatic osteoarthritis in the treatment of unstable syndesmotic injuries, anatomically correct reduction is crucial. The objective of the study was to investigate three different reduction methods of the ankle mortise in unstable syndesmotic injuries. In a specimen model with 38 uninjured fresh-frozen lower legs, a complete syndesmotic dissection was performed. The ankle mortise was reduced with either a collinear reduction clamp, a conventional reduction forceps or manually with crossing K-wires. The reduction clamps and the K-wires were placed in a 0°-angle to the leg axis. The clamps were positioned on the posterolateral ridge of the fibula 20 mm proximal to the ankle joint line. A cone beam computed tomography was performed after dissection and after each reduction. Tibio-fibular distances and angles were determined. Despite significant differences in terms of overcompression (0.09-0.33 mm; p = 0.000-0.063) and the slight external rotation (0.29-0.47°; p = 0.014-0.07), the results show a satisfying reduction of the ankle mortise. There were no considerable differences between the reduction methods. It can therefore be concluded that the ankle mortise can be reduced with any of the methods used, but that the positioning and the contact pressure must be considered.
Gesehen am 25.11.2019